Методологія відкритої економічної науки іноземною мовою: теорія та практика - Шмаровоз, Олена Василівна; Павлова, Олена Миколаївна; Ляшенко, Оксана Миколаївна; Матійчук, Любомир Павлович (Національний технічний університет "Харківський політехнічний інститут", 2024)
У сучасних умовах, коли наукові дослідження відіграють вирішальну роль у подоланні глобальних викликів, відкритість і загальнодоступність наукових знань стають основоположними принципами для успішного розвитку суспільства. Концепція відкритої науки, яка сприяє вільному обміну науковою інформацією, забезпеченню доступу до результатів досліджень, даних та методологій, створює нові перспективи для співпраці, інновацій та покращення якості наукової роботи. Для України, яка прагне посилити свій науковий потенціал і інтегруватися в глобальний науковий простір, розвиток відкритої науки є не просто важливим, а обов'язковим кроком для підвищення її конкурентоспроможності на світовій арені. Метою статті є ґрунтовне дослідження теоретичних та практичних аспектів дослідження методологічних засад відкритої економічної науки іноземною мовою. Матеріали та методи. Методологія відкритої науки стала одним із провідних напрямів сучасних наукових досліджень, спрямованих на підвищення доступності, прозорості та результативності наукової діяльності. Відкрита наука передбачає безкоштовний обмін знаннями, публікацію результатів досліджень у відкритому доступі та тісну співпрацю науковців з різних країн. Ці принципи особливо актуальні для міжнародних досліджень, де мовні та культурні бар'єри можуть стати перешкодою для ефективної взаємодії та обміну знаннями.

In today’s world, where scientific research plays a crucial role in addressing global challenges, openness and accessibility of scientific knowledge have become fundamental principles for the successful development of society. The concept of open science, which promotes the free exchange of scientific information and access to research results, data, and methodologies, creates new opportunities for collaboration, innovation, and improving the quality of scientific work. For Ukraine, which aims to strengthen its scientific potential and integrate into the global scientific community, developing open science is an important step toward enhancing its competitiveness on the world stage. By embracing open science, Ukraine can tap into a wealth of international knowledge, foster collaboration, and accelerate its scientific progress. The purpose of the article is to provide a thorough study of the theoretical and practical aspects of researching the methodological foundations of open economic science in a foreign language. Materials and Methods. The methodology of open science has become one of the leading directions in modern scientific research, focused on increasing the accessibility, transparency, and effectiveness of scientific activities. Open science involves the free exchange of knowledge, publication of research results in open access, and close collaboration between scientists from different countries. These principles are particularly relevant for international research, where language barriers, such as the need for translation and interpretation, and cultural differences, which can affect the interpretation and application of research findings, can hinder effective interaction and knowledge exchange. However, international collaboration is also a key strength of open science, as it allows researchers to leverage each other's expertise and resources, and to address global challenges more effectively.
Methodology of open economic science in a foreign language: theory and practice
Keywords: відкритий доступ; наукові дослідження; іноземні дослідження; репозитарій; open access; scientific research; foreign research; repository